2020
DOI: 10.3390/dairy1020008
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Fermented Milk with Collagen

Abstract: The aim of this study was to assess the possibility of using collagen protein hydrolysate in the production of milk fermented by Bifidobacterium animalis ssp. lactis Bb-12 and Lactobacillusrhamnosus. Physicochemical and organoleptic properties were studied and microbiological analysis of fermented milk was performed on days 1 and 21 of storage. Milk with the addition of 3% collagen protein hydrolysate was pasteurized (85 °C/30 min), divided into two groups, cooled to 37 °C and inoculated: the first group with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
8
0
4
Order By: Relevance
“…Moreover, extending the storage time to 21 days resulted in the highest increase in lactic acid concentration in samples fermented by L. casei compared to the other fermented milk samples. A similar correlation was shown by Znamirowska et al [ 40 ], and according to Kavaz and Bakirci [ 41 ], the amount of lactic acid in probiotic yogurts increases with storage time. In a study performed by Shori et al [ 42 ], the addition of fish collagen increased the initial titratable acidity (TA%) by about 0.2% lactic acid equivalent.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, extending the storage time to 21 days resulted in the highest increase in lactic acid concentration in samples fermented by L. casei compared to the other fermented milk samples. A similar correlation was shown by Znamirowska et al [ 40 ], and according to Kavaz and Bakirci [ 41 ], the amount of lactic acid in probiotic yogurts increases with storage time. In a study performed by Shori et al [ 42 ], the addition of fish collagen increased the initial titratable acidity (TA%) by about 0.2% lactic acid equivalent.…”
Section: Resultssupporting
confidence: 85%
“…A study by Znamirowska et al [ 40 ] of cow’s milk fermented by L. rhamnosus similarly showed higher pH values in milk with collagen hydrolysate compared to control samples during 21-day storage. A study by Dimitrellou et al [ 15 ] found that probiotic yogurts obtained from goat’s milk at 21 days of refrigerated storage had higher acidity (pH = 3.88) compared to those obtained from cow’s milk (pH = 3.98).…”
Section: Resultsmentioning
confidence: 98%
“…rhamosus were determined according to the method of Lima et al [ 22 ]. The inoculation was done by the plate method using MRS agar (Biocorp, Warszawa, Poland) and then incubated anaerobically with GENbox anaer (Biomerieux, Warszawa, Poland) in a vacuum desiccator at 37 °C for 72 h [ 23 ]. The colonies were counted using a colony counter (TYPE J-3, Chemland, Stagard Szczeciński, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…Continuing discussion on probiotic foods, adding collagen hydrolysate and açaí pulp improved the viscosity of milk beverages containing cheese whey, according to Rigoto et al [ 106 ]. Znamirowska and colleagues showed that collagen protein hydrolysate is able to increase gel hardness and reduce syneresis, as well as improve Bifidobacterium Bb-12 survival during storage [ 107 ].…”
Section: Proteinsmentioning
confidence: 99%